受体动脉不同临时阻断策略在烟雾病颞浅动脉-大脑中动脉搭桥术中的应用比较 Comparison of Different Temporary Occlusion Strategies for Recipient Arteries in the Application of Superficial Temporal Artery-Middle Cerebral Artery Bypass for Moyamoya Disease - 陈方舟，龙廷翰，陈俊达，温运宇，陈思源，张国忠，李明洲，张世超，康慧斌，冯文峰，漆松涛，王刚 (CHEN Fangzhou, LONG Tinghan, CHEN Junda, WEN Yunyu, CHEN Siyuan, ZHANG Guozhong, LI Mingzhou, ZHANG Shichao, KANG Huibin, FENG Wenfeng, QI Songtao, WANG Gang ) (Zhongguo cuzhong zazhi, 2024)
目的 探讨颞浅动脉-大脑中动脉端侧吻合术中不同临时阻断技术的效果及可靠性。